(untitled) (SENSISTEK:Riset Sains dan Teknologi Kelautan, 2022)
Maneuvering is a movement that is needed for a harbor tug to make moves such as towing, pushing or pulling ships that will dock. The limited water area in Indonesian ports affects the maneuvering and time efficiency required by a harbor tug. The use of propellers in a harbor tug is very influential for the sake of a port. This paper discusses simulation testing of ship maneuvers with Fixed Pitch Propeller and Azimuth Propeller carried out around Telok Lamong and Jamrud Port Surabaya. This simulation test can predict the ship’s maneuverability with variations in rotation angle.